Basin‐Width Dependence of Northern Deep Convection. Issue 15 (3rd August 2020) - Youngs, Madeleine K.; Ferrari, Raffaele; Flierl, Glenn R.
Abstract: Convection penetrates to the ocean bottom in the North Atlantic but not in the North Pacific. This study examines the role of basin width in shutting down high‐latitude ocean convection. Deep convection is triggered by polar cooling, but it is opposed by precipitation. A two‐layer analytical model illustrates that the overturning circulation acts to mitigate the effect of precipitation by advecting salty, dense water from subtropical latitudes to polar latitudes. The nonlinear dependence of the overturning strength on basin width makes it more efficient in a narrow basin, resulting in a convection shutdown at a stronger freshwater forcing. These predictions are confirmed by simulations with a general circulation model configured with a single closed basin to the north and a reentrant channel to the south. This suggests that basin width may play a role in suppressing convection in the North Pacific but not in the North Atlantic. Key Points: This study illustrates that basin size favors deep convection in the North Atlantic over the North Pacific A simple analytical model shows that convection shuts off for a weaker freshwater forcing per unit area in a wide basin compared to a narrow basin Single‐basin simulations with an ocean circulation model corroborate the prediction of the analytical model